You Need to Recognise Ambiguity to Avoid It. (20th November 2017) - Soo Hong, Chew; Ratchford, Mark; Sagi, Jacob S.
Abstract : After screening for attentiveness and comprehension, we present subjects with Ellsberg's (1961) two‐urn problem using essentially equivalent but representationally complex matrices. High‐comprehension subjects exhibit rates of ambiguity aversion typical of the standard two‐urn problem, while low‐comprehension subjects appear to randomise. In screening, we classify subjects as 'probability‐minded' or 'ambiguity‐minded', depending on whether they assign probabilities to draws from a card deck of unknown composition. Among high‐comprehension subjects, 'mindedness' explains twenty times more variation in ambiguity attitudes than all other demographic characteristics combined. Compared with their 'probability‐minded' counterparts, 'ambiguity‐minded' subjects are younger and more educated, analytic, and reflective about their choices.